1973
DOI: 10.1002/jcp.1040820103
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of calcium accumulation by lymphocytes and alterations in the process induced by phytohemagglutinin

Abstract: Calcium uptake by normal human lymphocytes was found to be a saturable process which was competitively inhibited by manganese indicating the existence of a carrier-mediated mechanism for calcium uptake. Exchange diffusion was not observed. Phytohemagglutinin (PHA) significantly stimulated calcium uptake within minutes after treatment. The increased uptake was attributed to a decreased K,,, for the proposed membrane carrier rather than to an increased V,,,.Also PHA did not stimulate a normally unused exchange d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A low pH depresses calcium uptake and the total cell calcium while a high pH does the reverse. This effect has been observed in liver (Wallach et al 1966), kidney (Rorive and Kleinzeller 1972;Studer and Borle 1979), fibroblasts (Lamb and Lindsay 1971), mast cells (Foreman et al 1977), lymphocytes (Whitney and Sutherland 1973), platelets (Steiner and Tateishi 1974), cardiac muscle (Morgenstern et al 1972), smooth muscle (Van Breemen et al 1972, and synaptosomes (BIaustein and Oborn 1975). No direct measurement of a pH effect on calcium influx in squid axon has been published, but Baker and McNaughton (1977) reported that a low pH depresses the Cao-dependent Na efflux linked to calcium influx.…”
Section: Voltage-independent Carrier-mediated Calcium Influxmentioning
confidence: 99%
See 1 more Smart Citation
“…A low pH depresses calcium uptake and the total cell calcium while a high pH does the reverse. This effect has been observed in liver (Wallach et al 1966), kidney (Rorive and Kleinzeller 1972;Studer and Borle 1979), fibroblasts (Lamb and Lindsay 1971), mast cells (Foreman et al 1977), lymphocytes (Whitney and Sutherland 1973), platelets (Steiner and Tateishi 1974), cardiac muscle (Morgenstern et al 1972), smooth muscle (Van Breemen et al 1972, and synaptosomes (BIaustein and Oborn 1975). No direct measurement of a pH effect on calcium influx in squid axon has been published, but Baker and McNaughton (1977) reported that a low pH depresses the Cao-dependent Na efflux linked to calcium influx.…”
Section: Voltage-independent Carrier-mediated Calcium Influxmentioning
confidence: 99%
“…In liver, kidney, and smooth muscle a rise in pH increases, while a low pH decreases, the total cell calcium (Wallach et al 1966;Rorive and Kleinzeller 1972;Van Breemen et al 1973;Studer and Borle 1979). The intracellular exchangeable calcium measured by 4s Ca uptake is also elevated by high pH and depressed at low pH in fibroblasts, lymphocytes, mast cells, smooth muscle, kidney, and Ehrlich ascites cells (Lamb and Lindsay 1971;Whitney and Sutherland 1973;Morgenstern 1972;Foreman et al 1977;Studer and Borle 1979;Hinnen et al 1979). In kidney cells, while acidosis depresses both total calcium and exchangeable calcium proportionately, alkalosis enhances the total calcium much more than the exchangeable calcium and most of the calcium gain is found in an unexchangeable pool, presumably in mitochondria (Studer and Bode 1979).…”
Section: The Role Ofphmentioning
confidence: 99%
“…Several different biochemical events have been described following shortly (within one hour) after exposure of lymphocytes to mitogens, but the possible causal relations of these events to the initiation of DNA synthesis are still poorly understood [ 1 ]. Phytohaemagglutinin (PHA) induces an increased influx of calcium ions through the plasma membrane into the cells within a few minutes [2,3], and calcium ionophore itself acts as a mitogen for lymphocytes [4][5][6]. Another early event is a considerable increase of the levels of cyclic guanosine 3':5' monophosphate (cGMP) in the cells, detected within minutes of exposure to PHA [7].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium mobiliza tion occurs rapidly upon stimulation [20], with the amount of calcium uptake directly related to DNA syn thesis [21], Reductions in either calcium influx or intra cellular calcium levels results in decreased levels of DNA and RNA synthesis [22], As tetracyclines are calcium and magnesium chelators, OTC-induced alterations in prolif eration are likely due, in part, to changes in intracellular and extracellular calcium levels.…”
Section: Discussionmentioning
confidence: 99%